2017
DOI: 10.1115/1.4036827
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Suction Flow Control Effectiveness in a Serpentine Intake

Abstract: The intakes of modern aircraft are subjected to ever-increasing demands in their performance. Particularly, they are expected to carry out diffusion with the highest isentropic efficiency while subjected to aggressive geometry requirements arising from stealth considerations. To avoid a penalty in engine performance, the flow through intake needs to be controlled using various methods of flow control. In this study, a serpentine intake is studied experimentally and its performance compared with and without bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This should enable the boundary layer to withstand higher adverse pressure gradients without separation. Keerthi et al (2017) have investigated suction to an S-duct at various positions and have shown that good values for the distortion parameters are obtained when suction is applied between 4% -5% inlet mass flow. Debiasi et al (2008) examined a moderate S-duct at different inlet Mach numbers and combined suction and blowing.…”
Section: Introductionmentioning
confidence: 99%
“…This should enable the boundary layer to withstand higher adverse pressure gradients without separation. Keerthi et al (2017) have investigated suction to an S-duct at various positions and have shown that good values for the distortion parameters are obtained when suction is applied between 4% -5% inlet mass flow. Debiasi et al (2008) examined a moderate S-duct at different inlet Mach numbers and combined suction and blowing.…”
Section: Introductionmentioning
confidence: 99%